2011
DOI: 10.1097/sle.0b013e31820ca3a4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transaxillary Subfascial Approach for Persistent Muscular Torticollis in Children

Abstract: The transaxillary endoscopic technique, a working cavern created under the fascia of the pectoralis major, offers a safe and straightforward way to surgically manage persistent muscular torticollis while preserving neurovascular structures, exempting extradissection of noninvolved tissues and avoiding the potential for poor cosmesis from any neck scar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Nevertheless, in our opinion, this technology has a higher risk of nerve injury. Dutta and Tang et al reported their technique of transaxillary subcutaneous endoscopic release of the sternocleidomastoid muscle for treatment of CMT [ 7 , 9 , 10 , 26 ]. Because the incision was made in the anterior axillary fold, a long subcutaneous tunnel over the clavicular and sternal heads of the SCM muscle was needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in our opinion, this technology has a higher risk of nerve injury. Dutta and Tang et al reported their technique of transaxillary subcutaneous endoscopic release of the sternocleidomastoid muscle for treatment of CMT [ 7 , 9 , 10 , 26 ]. Because the incision was made in the anterior axillary fold, a long subcutaneous tunnel over the clavicular and sternal heads of the SCM muscle was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Burstein described the original technique of endoscopic release for CMT for the first time in 1998 [ 4 ]. Several authors then reported different endoscopic release techniques for CMT [ 5 10 ]. The well-known advantage of endoscopy in contrast to the open operation is less traumatized and quick rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Konservatif tedaviden fayda görmeyen, ciddi deformitesi olan tedaviye dirençli KMT'li 3-5 yaş arası çocuklarda ise bipolar gevşetme uygulamasının sonuçları daha iyidir (2,37). Daha iyi kozmetik sonuç elde etmek için transaksiller subkütan endoskopik SKM divizyonu gibi endoskopik yaklaşımlar geliştirilmektedir (38,39). Operasyon ile boyun EHA düzelir ancak mevcut fasiyal asimetri ve skolyoz devam eder (40).…”
Section: Radyolojik İncelemeunclassified